2012
DOI: 10.1590/s1516-35982012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nile tilapia strains cultivated in cages under different feeding programmes

Abstract: -The objective of this study was to evaluate the performance of three Nile tilapia Oreochromis niloticus strains cultivated in cages and subjected to different feeding programmes. Initially, 31,200 Nile tilapia juveniles with an average weight of 61.15 g were distributed in 48 cages. Two genetically improved strains were used together with one from the Fish Culture Section of Universidade Federal de Lavras (UFLA). The fish were subjected to four feeding programmes, consisting of different levels of crude prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Overall, the best species to choose will depend on the goal of the breeding programme, as each species makes a greater or lesser contribution to the expression of certain traits. In this work, tambaqui seems to be the best option; however, other features that have not been evaluated, such as feed efficiency and production cost, are also important for defining the best genotype (Freato et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the best species to choose will depend on the goal of the breeding programme, as each species makes a greater or lesser contribution to the expression of certain traits. In this work, tambaqui seems to be the best option; however, other features that have not been evaluated, such as feed efficiency and production cost, are also important for defining the best genotype (Freato et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The main products for the fish processing industry are carcass, filet and ribs, so the species most appropriate for development of a breeding programme is pirapitinga, which had higher estimates of genetic value for these traits. However, industry is paid for a fish based only on its weight and not the bodily characteristics (Allaman et al., ; Freato et al., ), thus tambaqui remains the best alternative for breeding programmes. In addition, selection for body weight allows the indirect selection of animals with higher carcass, steak and trunk weights, and, considering that processing time is the same for any fish, large or small, a batch of heavier animals will generate a greater amount of meat than a batch of lean animals.…”
Section: Discussionmentioning
confidence: 99%
“…higher densities during shorter culture period tilapia reached commercial size (Marengoni, 2006;Carvalho et al, 2010;Freato et al, 2012). This poor growth may indicate that the cages were too close to the pond bottom, and the water quality in the studied pond was not good enough for the tilapias, or that 80 tilapia m -2 was a too high density for the fish under the water quality conditions prevailing in this flow-through system, or most probably a combination of all these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the fish fed with the diet containing formic acid and a mixture of propionic acid/salt in 2 g. kg -1 presented significant improvements in total body weight, weight gain, specific growth and feed conversion rates, in comparison with the other treatments. Freato et al (2012) submitted Nile tilapia (O. niloticus) juveniles to four feeding programs consisting of different levels of crude protein (PB) in different phases of cultivation and verified that the diets containing 36%, 32%, and 28% PB, respectively, promoted greater weight gain and final biomass. The same authors also observed that levels less than 36% PB in tilapia with weights between 60 and 170 g, as well as levels below 32% PB in tilapia with weights between 170 and 700 g negatively affected the performance of the fish.…”
Section: Fish Performance In the End Of The Experimentsmentioning
confidence: 92%